Mitonuclear discordance in wolf spiders: Genomic evidence for species integrity and introgression. Issue 7 (17th April 2018) - Ivanov, Vladislav; Lee, Kyung Min; Mutanen, Marko
Abstract: Systematists and taxonomists have benefited greatly from the emergence of molecular methods. Species identification has become straightforward through DNA barcoding and the rapid build‐up of massive DNA barcode reference libraries. In animals, mitonuclear discordance can significantly complicate the process of species identification and delimitation. The causes of mitonuclear discordance are either biological (e.g., introgression, incomplete lineage sorting, horizontal gene transfer androgenesis) or induced by operational factors (e.g., human error with specimen misidentification or incorrect species delimitation). Moreover, endosymbionts may play an important role in promoting fixation of mitochondrial genomes. Here, we study the mitonuclear discordance of wolf spiders species (Lycosidae) (independent cases from Alopecosa aculeata and Pardosa pullata groups) that share identical COI DNA barcodes. We approached the case utilizing double‐digest restriction site‐associated DNA sequencing (ddRADseq) to obtain and analyse genomic‐scale data. Our results suggest that the observed cases of mitonuclear discordance are not due to operational reasons but result from biological processes. Further analysis indicated introgression and that incomplete lineage sorting is unlikely to have been responsible for the observed discrepancy. Additional survey of endosymbionts provided ideas on further research and their role in shaping mitochondrial DNA distribution patterns. Thus, ddRADseq grants an efficient way to study the taxonomy of problematic groups with insight into underlying evolutionary processes.